Low-energy structure of isotopes 152-156Sm - Rosly, Noora; Okhunov, Abdurahim; Abu Kassim, Hasan (2012)
The 152–156Sm isotopes are classified as deformed nuclei. The phenomenological model is presented to describe the complete low – energy of 152–156Sm isotopes by taking into account the Coriolis mixing between states. The parameters fitted to the model are calculated. The energy spectra of positive – parity states are found to be in good agreement with the experimental data are presented. It is found that the non – adiabaticity of rotational energy bands occurred at high spin due to the Coriolis effect. Few new states are predicted.